A meta-analysis of the prevalence of Toxoplasma gondii in animals and humans in Ethiopia - Endrias Zewdu Gebremedhin; Getachew Tadesse (Parasites & Vectors, 2015)
Abstract Background Toxoplasmosis is a worldwide zoonosis. The objectives of this study were to estimate the prevalence and assess the potential risk factors of Toxoplasma gondii infections in animals and humans in Ethiopia by using meta-analytical methods. Methods Published studies on T. gondii in animals and humans in Ethiopia were searched in Medline, Google Scholar and the lists of references of articles. Eligible studies were selected by using inclusion and exclusion criteria. The risks of within and across study biases, and the variations in prevalence estimates attributable to heterogeneities were assessed. Pooled prevalence was estimated by the DerSimonian and Laird random effects model. Results Thirty two studies were eligible and data from 5689 animals and 5718 humans were used for quantitative syntheses. The pooled IgG seroprevalence in cats, small ruminants and humans were estimated at 87.72 % (95 % CI = 78.63, 93.28), 34.59 % (95 % CI = 21.08, 51.12) and 74.73 % (95 % CI = 61.85, 84.36), respectively. The odds of infections were higher in pregnant than in non pregnant women (OR = 3.96), in individuals that had contact with cats than those with no contact (OR = 2.53), and in urban than in rural inhabitants (OR = 2.06). Conclusions Toxoplasmosis is highly prevalent and could be a cause of considerable reproductive wastage in small ruminants and multiple diseases in humans in Ethiopia. Public education on preventive measures could help reduce the transmission of the parasite to humans.